A Empirical Experience as an Idea of Creating Performing Arts Can Be Used as Self-Introspection, Self-Relaxation, and Self-Reflection for the Audience - Iin, Iin Suminar (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
Life is filled with experiences that leave lasting impressions—joyful, sorrowful, or challenging moments that shape an individual’s perspective and are often worth sharing. These empirical experiences, derived from personal encounters, observations, or narratives, can serve as valuable principles for others. This study explores how such experiences can inspire the creation of performing arts, aiming to transform personal realities into engaging and meaningful artistic expressions. By drawing on empirical experiences, performing arts can become a medium for introspection, relaxation, and self-reflection, offering both creators and audiences opportunities for deeper emotional and intellectual engagement. Using a qualitative approach, this research gathers data through interviews and documentation of performance works that utilize empirical experiences as creative inspiration. The findings reveal that performances rooted in real-life experiences not only generate new knowledge but also provide therapeutic benefits for the artists, enabling them to process and release personal anxieties. This transformation of anxiety into knowledge highlights the dual role of performing arts as both a creative and an educational tool. Moreover, the study emphasizes the significance of empirical experiences in producing authentic and impactful performances that resonate with audiences, fostering shared understanding and emotional connections. This research underscores the importance of integrating empirical experiences into artistic creation, demonstrating their potential to enrich the performing arts with authenticity, introspection, and cultural relevance, while contributing to the artist’s personal growth and societal knowledge dissemination.